EVALUATION OF HYPERTENSION PREVENTION & MANAGEMENT STRATEGIES: THE IMPACT OF ANTIHYPERTENSION BEVERAGES AND MORINGA TEA ON MOOD DEVELOPMENT AND IMMUNITY - Jayadi, Yusma Indah; Hasbi Ibrahim; Nadyah Haruna (Universitas Islam Negeri Alauddin Makassar, 2025)
Background: Takalar Regency in 2017 the number of hypertension sufferers was 2969 (80%) with 927 men (28%) and 1769 women (61%). Moringa is one of the assets in Maccini Baji Hamlet. It is known that the Moringa plant contains all the nutrients needed to balance blood pressure. Objective: The purpose of this study was to evaluate education related to the prevention and management of hypertension as well as to foster the atmosphere of antihypertensive drinks from Moringa leaves. Method: This research is a quantitative study using purposive sampling technique related to counseling on the prevention and control of hypertension and building an atmosphere for antihypertensive drinks carried out by observation and in-depth interviews related to knowledge, attitudes and actions. Result: The results of the study proved the effect of the boiled water of Moringa leaves on blood pressure in hypertensive patients. The Wilcoxon Statistical Test was carried out at a significance level of α (0.05) with a (p) value of 0.000, so it can be said that there was a significant change between the Moringa leaf decoction and changes in blood pressure in hypertensive patients. Conclusion: Based on the analysis of the Friedmen test, it showed a significant value of 0.000 (p <0.05) so that it can be concluded that there was an increase before and after three months of counseling on prevention and control of hypertension.